Nrf2 Is Required for Optimal Alveolar-Macrophage-Mediated Apoptotic Neutrophil Clearance after Oxidant Injury - Narsa M. Reddy; Chandra Mohan Tamatam; Ankireddy Aparna; Sekhar P. Reddy (MDPI AG, 2022)
Recognition and clearance of apoptotic cells by phagocytes (also known as efferocytosis), primarily mediated by macrophages, are essential to terminate lung inflammatory responses and promote tissue repair after injury. The Nrf2 transcription factor is crucial for cytoprotection and host defense. Previously, we showed sustained neutrophilic lung inflammation in Nrf2-deficient (Nrf2−/−) mice after hyperoxia-induced lung injury in vivo, but the mechanisms underlying this abnormal phenotype remain unclear. To examine whether Nrf2 regulates apoptotic neutrophil clearance, we used the alveolar macrophages (AMФs) and bone-marrow-derived macrophages (BMDMФs) of wild-type (WT) and Nrf2−/− mice. We found that the efferocytic ability of AMФ was impaired in hyperoxia-exposed mice's lungs, but the effect was more pronounced in Nrf2−/− mice. Importantly, AMФ-mediated efferocytosis remained impaired in Nrf2−/− mice recovering from injury but was restored to the basal state in the wild-type counterparts. Hyperoxia affected apoptotic neutrophil binding, not internalization, in both WT and Nrf2−/− BMDMФs, but the effect was more significant in the latter cells. Augmenting Nrf2 activity restored hyperoxia attenuated efferocytosis in WT, but not in Nrf2−/− macrophages. However, the loss of Nrf2 in neutrophils affected their uptake by WT macrophages. Collectively, these results demonstrate that Nrf2 is required for optimal macrophage-mediated efferocytosis and that activating Nrf2 may provide a physiological way to accelerate apoptotic cell clearance after oxidant injury.